Walras, Leontief, and the Interdependence of Economic Activities: Comment - Henderson, James M.; Quandt, Richard E. (Quarterly Journal of Economics, 1955)
Journal Article Walras, Leontief, and the Interdependence of Economic Activities: Comment Get access James M. Henderson, James M. Henderson Harvard University Search for other works by this author on: Oxford Academic Google Scholar Richard E. Quandt Richard E. Quandt Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 4, November 1955, Pages 626–631, https://doi.org/10.2307/1881999 Published: 01 November 1955